Respon Pertumbuhan Miselia Beberapa Isolat F3 Jamur Merang (Volvariella volvaceae) FAPERTA UNSIKA pada Media PDA dan Air Cucian Beras Merah (Oryza nivara) - Saputra, Yulianto Hadi; Lestari, Ani; Laksono, Rommy Andhika; Rianti, Winda (JURNAL AGROPLASMA, 2024)
The success of cultivating straw mushrooms depends on the quality of the mushroom spawn. In addition to genetic factors, the nutrients present in the growth medium also influence the growth of straw mushroom spawn. The study was conducted in the Biotechnology and Plant Breeding Laboratory of the Faculty of Agriculture, Singaperbangsa Karawang University, located in Karawang Regency, from June 2023 to July 2023. The research method used was experimental with a Randomized Block Factorial Design. There were 2 factors consisting of 21 treatments. The first factor was in vitro culture media, consisting of 3 levels, namely, m1 (PDA 100%), m2 (ACBM 100%), and m3 (PDA 50% + ACBM 50%). The second factor was the straw mushroom isolates from Faperta Unsika, consisting of 7 levels, namely, i1 (Parent P), i2 (Parent S), i3 (FP0025), i4 (FP0026), i5 (FP0027), i6 (FP0034), and i7 (FP0047). Each treatment was replicated 3 times, resulting in 63 experimental units. The treatment effects were analyzed using analysis of variance (ANOVA), and if the F-test was significant, the best treatment was determined using DMRT at the 5% significance level. The results showed an interaction between the three different in vitro media and several isolates of F3 straw mushrooms (Volvariella volvaceae) from Faperta Unsika on mycelial colony diameter and mycelial growth rate. Treatment with the straw mushroom isolate (Volvariella volvaceae) Faperta Unsika FP034 on the medium (PDA 50% + ACBM 50%) resulted in the highest mycelial growth with a colony diameter of 8 cm and a mycelial growth rate of 2.22 cm/day on day 1 to day 2. Keywords: mycelia, isolate faperta unsika, straw mushroom, media nutrision, red rice wash water media